Age is a critical determinant in recovery from multiple sclerosis relapses. (November 2019) - Conway, Brittani L; Zeydan, Burcu; Uygunoğlu, Uğur; Novotna, Martina; Siva, Aksel; Pittock, Sean J; Atkinson, Elizabeth J; Rodriguez, Moses; Kantarci, Orhun H
Objective: To evaluate the impact of age on recovery from multiple sclerosis relapses. Background: Increasing disability in multiple sclerosis is a consequence of progressive disease and incomplete relapse recovery. Methods: The first and last-ever relapse data (357 relapses in 193 patients) from the Olmsted County population-based multiple sclerosis cohort were systematically reviewed for age, fulminance, location (optic nerve, brainstem/cerebellar, spinal cord), peak deficit, and maximum recovery. Three different relapse-outcome measures were studied both as paired analyses and as an overall group effect: change from peak deficit to maximum recovery in raw functional system score related to the relapse (ΔFSS), a previously published FSS-based relapse-impact model, and change from peak deficit to maximum recovery in Extended Disability Status Scale (ΔEDSS) score. Results: Older age was linearly associated with worse recovery in the ΔFSS outcome ( p = 0.002), ΔEDSS outcome ( p < 0.001), and the FSS-based relapse-impact model ( p < 0.001). A multivariate analysis of ΔFSS outcome linked poor recovery to older age ( p = 0.015), relapse location (transverse myelitis or brainstem/cerebellar syndrome; p < 0.001), and relapse fulminance ( p = 0.004). Conclusion: Multiple sclerosis-relapse recovery declines in a linear fashion with increased age, which should be considered when making treatment decisions.